If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 83 = 2(-6b + 1) + -3 Reorder the terms: 83 = 2(1 + -6b) + -3 83 = (1 * 2 + -6b * 2) + -3 83 = (2 + -12b) + -3 Reorder the terms: 83 = 2 + -3 + -12b Combine like terms: 2 + -3 = -1 83 = -1 + -12b Solving 83 = -1 + -12b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12b' to each side of the equation. 83 + 12b = -1 + -12b + 12b Combine like terms: -12b + 12b = 0 83 + 12b = -1 + 0 83 + 12b = -1 Add '-83' to each side of the equation. 83 + -83 + 12b = -1 + -83 Combine like terms: 83 + -83 = 0 0 + 12b = -1 + -83 12b = -1 + -83 Combine like terms: -1 + -83 = -84 12b = -84 Divide each side by '12'. b = -7 Simplifying b = -7
| (3/7)x-1=(2/ | | 11k=13t−7k/2t | | 1+Log[5](-4x)=3 | | 544=-5n-8(7n-7) | | (3z-5)(7-z)=0 | | 2/3y-6=10 | | 3x-4(-2x-5)=2x-3 | | 5x^2+6-51=0 | | h-4+1=3 | | 8(3x-5)=-64 | | ln(17+2x)=2ln(x+1) | | 7/7=3 | | -2x-5(4x+3)=3x | | 26=10h/18 | | 11.5x+12=161.50 | | 3(-2y)+7y=1 | | 5t=56 | | c=12+11.5t | | 9x-6(x-2)=6+x+20 | | (9x-6)+(-8x+4)=7 | | 2x+x^2=0.051216343 | | sqrt(60)*sqrt(y/4) | | v/9=3/7 | | (4a+4b+4c)(4a+4b+4c)= | | 86=-5-7(-4n-5) | | 30+50x=65x | | 17.42(p)=8.71 | | 4.13-0.54x=5x-2.795 | | 2w+8x-15y+7w+7x+8y= | | 3(1+-0.5y)+4y=-7 | | 5x+4y+9=0 | | x+16-64= |